AN ANALYSIS OF HIGHER ORDER THINKING SKILL IN READING SKILL AT ENGLISH DEPARTMENT 2018 - Rahayu, Imelda Wati Putri; Fitriawati, Fitriawati (Borneo Journal of English Language Education, 2022)
The objective of this research was obtain empirical evidence from the distribution of Higher order thinking skills based on the revised edition of Bloom’s Taxonomy on multiple choices questions in reading test items in reading skill at English department 2018.This research was conducting by using content analysis method, because the researcher identifies the specific characters of the material in reading multiple choices questions in reading test items. This research uses qualitative data because the data is in the form of words. The object of this research was the reading multiple choices in reading test items at English department 2018. The data was collected through several instruments, namely the exercises sheet of reading test items, interview, checklist table and Bloom’s taxonomy guidelines. The result of this research showed that, the higher order thinking skills in reading skill at English department obtained 11 out of 25 questions in reading multiple choices (44%) while the lower order thinking questions obtained 14 of 25 reading multiple choices questions (56%). The result of the distribution of higher order thinking skills were : analyze skills get the highest distribution, 6 of 25 multiple choices questions in reading test items (24%), evaluating skills get 4 out of 25 questions in reading test items (16%), create skills get 1 out of 25 questions in reading test items (4%). Overall, it concluded that the distribution of the higher order thinking skills is lower than lower order thinking skills.